Hubungan Pengetahuan Sikap Dan Dukungan Suami Dengan Penggunaan Metode Kontrasepsi Suntik 3 Bulan Di PMB Ny D Desa Hegarmanah Kecamatan Sukaluyu Kabupaten Cianjur : The Relationship between Knowledge, Attitude and Support of Husbands with the Use of the 3-Month Injection Contraceptive Method in PMB Mrs. D. Hegarmanah Village, Sukaluyu District, Cianjur Regency - Fatimah, Sarah Siti (Dohara POAJ, 2024)
Introduction: Injectable contraception is a contraceptive device in the form of a liquid containing hormones that is injected into a woman's body periodically. Meanwhile, 3-months injectable contraception is an injectable type of hormonal contraception containing Depot Medroxyprogesterone Acetate (DPMA) at a dose of 150 mg/ml intramuscularly (IM) every 12 weeks. Methods: This research method uses quantitative methods with a cross-sectional design. The data collection was carried out by distributing questionnaires. The analysis used is univariate and bivariate with the chi-square test using the SPSS application. Results: In this study, each question item had a calculated r > r table (0,238) and had a positive value. Thus, the question item was declared valid with Cronbach's Alpha of knowledge, attitude and husband's support > 0,60 thus, it could be said to be reliable. Univariate analysis good knowledge has a frequency of 45 with the percentage of 66% and poor knowledge has a frequency of 23 with the percentage of 34% for 3-months injection contraceptive use. Unfavorable attitudes have a frequency of 22 with a percentage of 32% and respondents who have a favorable attitude have a frequency of 46 with a percentage of 68%. supported has a frequency of 40 with the percentage of 59% and not supported has a frequency of 28 with the percentage of 41%. Bivariate analysis of respondents who have good knowledge namely 57%; to use contraceptive methods for 3 months with a result of p = 0,000; unsupportive attitude namely 26% for using contraceptives for 3 months with p = 0,012 < 0,05; not supported by husbands namely 26% for use 3 months contraception with p = 0,017 < 0,05. Discussion: In this discussion the variable impact of attitudes towards the use of the 3-months contraceptive method for the 3 months contraceptive injection in PMB Mrs. D. having a relationship. With a p-value = 0,012 < 0,05 this means that there is a relationship between an unsupportive attitude and the use of contraceptives for 3 months with an OR value = 31,67 which means that mothers with an unsupportive attitude have 31 times more repeat cases compared to mothers who have a supportive attitude.